Evaluation of infant and young child feeding practices in low-income areas of Dhaka, Bangladesh: insights from a cross-sectional study using the 2021 WHO/UNICEF guideline - Saiful Islam; Sadia Sultana; Tasmia Tasnim; Kazi Muhammad Rezaul Karim; Md Hafizul Islam; Ali Abbas Mohammad Kurshed (BMJ Open)
Objective This study aimed to assess the status of infant and young child feeding (IYCF) practices and associated factors among children aged 0–23 months in the low-income regions of Dhaka City, Bangladesh.Design A community-based cross-sectional study.Settings Low-income regions of Dhaka City, Bangladesh.Participants 530 children aged 0–23 months and their mothers.Primary and secondary outcome measures Prevailing IYCF practices were assessed against the 17 indicators of IYCF recommended by the WHO/UNICEF in 2021. Modified Poisson regression models were built to explore the relation between socio-demographic variables and each of the selected IYCF indicators (early initiation of breastfeeding (EIBF), exclusive breastfeeding (EBF), minimum dietary diversity (MDD), minimum meal frequency (MMF) and minimum acceptable diet (MAD)).Results More than two-thirds of the children were reported to follow appropriate breastfeeding practices (EIBF, 70.4% and EBF, 60.9%). Among the complementary feeding indicators, almost half of the children (48.8%) were reported to meet MMF; however, only about 26% of the children reportedly met the MDD with a consequent low prevalence (22.9%) of the composite indicator MAD. More than half (55%) of the children were reported to consume egg and/or flesh food consumption; still, inappropriate dietary practices were observed among 60% had unhealthy food consumption, and 56% had zero vegetable or fruit consumption). Child age was a significant determinant of IYCF practices. The children of mothers with no pregnancy complications exhibited a greater chance of having EIBF (estimate: 1.21, 95% CI: 1.04, 1.42, p=0.02), MDD (Estimate: 1.67, 95% CI: 1.09, 2.55, p=0.02), and MAD (estimate: 1.70, 95% CI: 1.04, 2.77, p=0.03) compared with the children of mothers with pregnancy complications. The children with a mother having secondary or higher education had a higher chance of having MDD (estimate: 1.93, 95% CI: 1.35, 2.76, p=0.003) and MMF (estimate: 1.27, 95% CI: 1.03, 1.56, p=0.02) than the children of mothers having primary or no education. Similarly, children from higher-income households had a higher chance of getting MDD (estimate: 1.57, 95% CI: 1.07, 2.03, p=0.02), and MAD (estimate: 1.73, 95% CI: 1.14, 2.64, p=0.01) compared with children from lower-income households.Conclusion IYCF practices among a considerable proportion of children aged 0–23 months in the low-income regions of Dhaka City were found to be suboptimal and predicted by children’s age, maternal education and pregnancy complications, and household income.